Investigating the Teachers’ Perceptions toward the Use of L1 in Teaching English - Dodi Widia Nanda (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study explores the teachers’ perceptions of using the first language (L1) when teaching English. The conceptual work of literature review is applied as the research method. This means previous works were analysed to investigate teachers’ perceptions toward the L1 use in teaching English. The result shows that the L1 can be used in teaching grammar, vocabulary, and giving instructions. Teachers are also divided into three positions in perceiving the use of L1 in teaching English, which are the virtual, maximal, and optimal position. Therefore, teachers might use this study’s results as the information to use the L1 in classrooms. This may also be beneficial for Indonesian educational stakeholders and the government to specifically define the use of L1 in teaching English.